디지털 기반 교수-학습 지식습득을 위한 교사교육 프로그램: 미국 N대학 교육공학과 사례를 중심으로 - 이한나; Lee, Hannah (한국콘텐츠학회 논문지, 18(2), 2018)
The study introduced an actual American university program student's learning outcomes in instructional technology integration knowledge in order to acknowledge implication considering the current status of relevant Korean teacher training programs. With utilizing complete sampling (students enrolled in a master's program in Instructional Systems Technology at the N University in Fall 2015), the survey was conducted on knowledge, strategies and performance in instructional technology integration, and interview assessed deeper understanding of students' relevant competencies in their specific professional setting. The results and findings based on triangulation of the data confirmed that the students gained sufficient knowledge, and applied the relevant knowledge and competencies into their work setting. For future research, the implications were offered on reviewing Korean teacher training programs in professional competency development related to technology integration in teaching and learning. 본 연구는 대학의 교과과정을 통한 학생들의 디지털 기반 교수-학습 개발 프로그램을 지식 측면에 집중하여, 미국의 실제 교육사례를 소개함으로 한국의 디지털 기반 교수-학습 교사교육 실태와 더불어 시사점을 찾고자 수행되었다. 2015년 가을학기 미국 N대학 교수시스템공학 석사 프로그램에 등록한 학생들 전원을 대상으로 설문하여 디지털 기반 교수-학습 지식, 전략 및 활용에 대하여 그 학습결과를 조사하였으며, 학기말 이들의 실제 업무와 관련해 디지털 기반 교수-학습 역량에 대한 심층적인 내용을 인터뷰하였다. 또한, 실제로 사용한 강의 계획안을 수집하여 연구 참여 학생들의 실제 수업 과정을 구조적으로 파악하였다. 이와 같이 다각화를 통해 프로그램 교과과정의 디지털 기반 교수-학습 교육의 실효성을 분석 및 평가하였다. 그 결과 학생들이 디지털 기반 교수-학습 활용 지식을 충분히 습득하였으며, 이를 그들이 실제 근무지에서 적용하여 역량을 발휘하는 데 적절한 도움이 되었음을 확인할 수 있었다. 이 사례와 준하여 국내 학술연구 속의 한국 현직교사 및 예비교사들의 교육 프로그램의 실태 및 실제 사례를 바탕으로 한국의 디지털기반 교수-학습 교사교육에 대한 시사점 및 후속연구에 대한 제언을 논의하였다.